2004
DOI: 10.1007/s00125-004-1394-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of key genes of fatty acid oxidation, including adiponectin receptors, in skeletal muscle of Type 2 diabetic patients

Abstract: Aims/hypothesis. Defective oxidation of long-chain fatty acids is a feature of insulin resistance and Type 2 diabetes. Our aim was to compare the expression levels of the genes encoding the major proteins and enzymes of this pathway in skeletal muscle of healthy subjects and Type 2 diabetic patients. Methods. The basal and insulin-regulated mRNA concentration of 16 genes was quantified using real-time PCR in skeletal muscle biopsies taken before and at the end of a 3-hour hyperinsulinaemic-euglycaemic clamp in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 41 publications
8
79
2
2
Order By: Relevance
“…Interestingly, we observed that refeeding carbohydrate did not change adipoR1 or adipoR2 expression in humans. Other studies in humans have shown that the adipoR1/R2 expression is not changed after insulin infusion (44) or after insulin addition to primary muscle culture (45). Together, these findings strongly suggest that adipoR expression is not regulated by glucose or insulin in humans.…”
Section: Figmentioning
confidence: 56%
“…Interestingly, we observed that refeeding carbohydrate did not change adipoR1 or adipoR2 expression in humans. Other studies in humans have shown that the adipoR1/R2 expression is not changed after insulin infusion (44) or after insulin addition to primary muscle culture (45). Together, these findings strongly suggest that adipoR expression is not regulated by glucose or insulin in humans.…”
Section: Figmentioning
confidence: 56%
“…The mRNA expression of (a) PHLPP1 and (b) PHLPP2 was determined by quantitative real-time PCR, as described in the Methods section. Vastus lateralis muscle samples were obtained from age-matched healthy control subjects (white bars) and type 2 diabetic patients (black bars) [32]. *p=0.024 comparing PHLPP1 mRNA expression in biopsies from control subjects vs diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of PHLPP1/2 mRNAs PHLPP1 and PHLPP2 mRNA expression was measured by reverse transcription followed by real-time PCR, using a Light-Cycler (Roche Diagnostics, Meylan, France), in total RNA preparations from human skeletal muscle samples obtained in a previous study from control and type 2 diabetic patients with similar characteristics to those included in the present work [32]. First-strand cDNAs were synthesised from 500 ng total RNA in the presence of 100 units Superscript II (Invitrogen, Cergy Pontoise, France) using both random hexamers and oligo (dT) primers (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…ADIPOR1 is a highaffinity receptor for globular adiponectin, while ADIPOR2 is an intermediate-affinity receptor for both globular and full-length adiponectin (7,29). Expression of ADIPOR1 and ADIPOR2 has been associated with insulin resistance (32) and was found to be lower in diabetic and normal glucosetolerant subjects with family history of diabetes (10,30).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of ADIPORs may blunt adiponectin-induced signaling (7). The expression of adiponectin receptor has been related to in vivo parameters of glucose and lipid metabolism (9) and was found to be lower in diabetic patients (10). The polymorphisms in the ADIPOR1 gene were recently associated with adiposity, insulin resistance, and high liver fat (11)(12)(13).…”
mentioning
confidence: 99%